The Differences in the Effectiveness of Pilates Exercises and Bobath Exercises on Sitting and Standing Balance in Children with Cerebral Palsy - Suharto Suharto; Sri Saadiyah Leksonowati; Hasnia Ahmad; Suriani Suriani (Jurnal Penelitian Pendidikan IPA, 2023)
This study aimed to analyze the effectiveness of Bobath and Pilates exercises on sitting and standing balance in children with cerebral palsy. It utilized a quasi-experimental study design with a two-group pre-test-post-test design. The study included 66 children with cerebral palsy, aged 1-7 years, who were randomly divided into two groups: 33 children received Pilates exercises, and 33 children received Bobath training. The intervention was conducted once a day, three times a week, for 45 minutes over a 16-week period. The results of the paired t-test statistics indicated that Pilates exercises significantly improved sitting balance (p = 0.002) but had no significant effect on standing balance (p = 0.083). On the other hand, Bobath exercises significantly improved both sitting balance (p = 0.001) and standing balance (p = 0.023). Independent t-test results for sitting balance yielded (p = 0.039), and for standing balance (p = 0.034) In conclusion, there were significant differences in both sitting balance and standing balance between the group that underwent Pilates exercises and the group that received Bobath exercises in children with cerebral palsy